Processing Chank Meat (Xancus pyrum) into Pickles - K., Dhanapal; K., Rathnakumar; G., Indra Jasmine; P., Jeyachandran (Fishery Technology, 2025)
Methods have been worked out for the production of pickles from Chank (Xancus . pyrum) meat. The pickle was subjected to biochemical, bacteril)logical and organoleptic tests at different intervals of storage. The chank meat pickles packed in glass bottles and sealed air tight remained in good condition for six months at ambient temperature.